Fenomena percampuran kod dalam iklan perniagaan bahasa Cina di Malaysia / Lau Su Kia - Lau, Su Kia (2007)
This research was conducted to study the phenomenon of code mixing in Malaysian Chinese business advertisements. Specifically, it aimed to identify the English lexical items and their characteristics mixed into the title and descriptive sentences and the factors leading to the emergence of the mixture of such English lexical items being into local Chinese commercial advertisements. The data were collected from four Chinese newspapers in Malaysia, namely China Press, Guang Ming Daily, Nanyang Siang Pau and Oriental Daily. A total of 100 titles and descriptive sentences of Chinese commercial advertisements mixed with various English lexical items were selected for analysis. In addition, a total of 100 questionnaires were distributed to the study sample and a follow-up interview was conducted among five local Chinese advertisement writers. Both quantitative and qualitative approaches were used in this study. It was found that the mixture of English nouns, abbreviations, adjectives and verbs outnumbered exclamations and prepositions in this study. While some of these English proper nouns have no equivalent nouns in Chinese, and others have equivalent nouns. Such mixture of English abbreviations, adjectives, and verbs seems to be intended by users to simplify the title and description sentences of the advertisements for readers/customers while saving the newspaper space and readers’ time at the same time. The mixing of “No.1” aimed at highlighting the advertised business product is top-notch. Some of the mixed English adjectives are stylish, modern in character, and suit the tastes of the younger generation. The mixture of adjectives is intended to attract the attention and interest of young people to purchase the advertised commercial products. Interestingly, the English abbreviations “SMS” and “MMS” also function as verbs, and “hit” has changed its function into an adjective after being mixed into local Chinese advertisements. Furthermore, the mixed English exclamations “wow” and “yeah” make the title and description sentences of the Chinese advertisement more verbal and more easily accepted by the readers. The results indicate that English lexical items that are frequently mixed into speech among Chinese language users in Malaysia are also mixed into Malaysian Chinese business advertisements. The findings of this study contribute to the field of advertising and provide valuable implications for research.